Bottled water consumption in Mexico in view of a circular economy - Silva, Jorge; Monroy, Dulce; Martínez, Esteban (Tecnología y ciencias del agua, 2024)
The objective is to analyse bottled water consumption in Mexico in view of a circular economy. The paper evaluates the rates of bottled water consumption and the key causal factors. Furthermore, it compares the role played by the private and public sectors in exacerbating demand for bottled water. The paper implemented a systematic review that identified articles mainly from the Web of Science and Scopus databases from November 01 to December 31, 2022. There were utilised three strategies for the search process, including keying in free-text words, implementing Boolean operators, and citation searching. The systematic review was conducted in line with the PRISMA statement/methodology. Forty-eight articles were identified after the complete search. The summations direct that bottled water consumption is high in Mexico due to the below-par conventional drinking water supply. Most customers cited organoleptic and health reasons as key factors influencing their preference for bottled drinking water. Conversely, the demand for bottled water contributes to high Polyethylene Terephthalate bottles, which contribute to environmental degradation. The implementation of the circular economy can reduce the associated negative effects through decreasing and optimization strategies. There were conglomerates findings from various articles while defining the key gaps and areas for improvement. The paper is seminal in bridging the dearth of knowledge on the circular economy and its application in the water industry while providing recommendations for policymakers.